PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NHTUNTUK MENINGKATKAN HASIL BELAJAR PKn SISWA KELAS VISDN 004 SIMPANG PULAI KECAMATAN UKUIKEBUPATEN PELALAWAN - Slamet Riyadi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
The background of this study is the low learning outcomes PKn students of class VI SDN 004 Desa Simpang Pulai Kecamatan Ukui, that of the 30 students, only 15 students who completed the learning outcomes PKn, with the average value of 54 where KKM specified is 70 , 00. The cause of low learning outcomes is the passivity of students in the learning process, In addition, teachers are still using conventional teaching methods and teacher-centered. Based on this, the researchers conducted an increase learning outcomes through the application of the model. This study is a class action that aims to improve learning outcomes PKn as well as increase the activity of students in the learning process through the implementation of NHT type cooperative model. Data collection techniques used were observation activities of teachers and students, achievement test, and documentation. This study was conducted over two cycles. The data in this research is descriptive about the activities of teachers and students and learning outcomes in subjects PKn class VI student. The results of this study showed that the learning outcomes PKn increased each cycle. Preliminary data states that only 15 students or 50% were completed, the first cycle of mastery learning increased with the number of 26 students or 87%, and the second cycle increased mastery learning again with the number of 27 students or 90%.